Study on the Impact of Information Technology Transport Infrastructure on Logistics Transport Development: The Case of Ho Chi Minh, Vietnam - Hanh, Vu Thi Kim (Modern Perspectives of Logistics Transport in Economics. Empirical Studies in Ho Chi Minh, Vietnam Vol. 2, 2021)
Our lives today are heavily dependent on information technology. Especially economic activities, logistics transport sector is not exception. The objective of paper is to measures the role of information technology infrastructure (ITI) in development of logistics transport by assessing the impact of six independent variables of ITI on logistics transport development which using multivariate regression (MR). The main findings are Labour goods productivity is impacted by number of broadband subscriptions and international internet traffic. Labour passenger productivity is impacted by number of safe Internet connections and number of broadband subscriptions. Capital goods productivity is impacted by number of safe Internet connections and number of ADSL internet subscribers. Gross domestic product is impacted by number of ADSL internet subscribers, international internet traffic and number of mobile network subscriptions.